Pengaruh Kebijakan Pengenaan Bea Masuk Tindakan Pengamanan Terhadap Impor Produk Kain (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2002)
This study aims to examine the effect of the policy of imposing security measures on imports of fabric products. This study uses a normative juridical research method using secondary data. The novelty element in this research lies in the focus of the discussion which specifically discusses the influence of the policy of imposing security measures on imports of fabric products. The research discussion states that the principles of international trade adopted by the Indonesian state, namely the protection of domestic products, and the imposition of security measures on imports of fabric products, are the embodiment of the principle of trade in the Indonesian state. Based on the results of the study, it was concluded that the effect of imposing additional import duties in the form of security measures through the Minister of Finance Regulation No.55/PMK.010/2020 on the import of fabric products is less effective because it will only burden local entrepreneurs who need material products from abroad. Even though there have been restrictions on the volume of imports of textiles and textile products, so that these inter-ministerial regulations have not been able to synergize, the existence of legal rules regarding the imposition of BMTP makes the Ministry of Finance seem to doubt the Ministry of Trade's policy to suppress imports of fabric products in the free market era. Keywords: import duty security measures; cloth; liberalization; international trade Abstrak Penelitian ini bertujuan untuk mengkaji pengaruh kebijakan pengenaan Bea Masuk Tindakan Pengamanan terhadap impor produk kain. Penelitian ini menggunakan metode penelitian yuridis normatif dengan menggunakan data sekunder. Unsur kebaharuan dalam penelitian ini terletak pada fokus pembahasannya yang secara spesifik membahas tentang pengaruh kebijakan pengenaan bea masuk tindakan pengamanan terhadap impor produk kain. Pembahasan penelitian menyatakan bahwa prinsip perdaganagan internasional yang dianut negara Indonesia yaitu perlindungan produk dalam negeri, dan pengenaan Bea masuk tindakan pengamanan terhadap impor produk kain merupakan perwujudan dari prinsip perdagangan negara Indonesia. Berdasarkan hasil penelitian disimpulkan bahwa pengaruh pengenaan bea masuk tambahan berupa bea masuk tindakan pengamanan melalui Permenkeu No.55 /PMK.010/2020 terhadap impor produk kain kurang efektif karena hanya akan memberatkan pengusaha lokal yang membutuhkan produk bahan dari luar negeri. Padahal telah dilakukan pembatasan volume impor tekstil dan produk tekstil, sehingga peraturan antar Kementerian ini belum dapat bersinergi, dengan adanya aturan hukum mengenai pengenaan BMTP menjadikan Kementerian Keuangan seolah-olah meragukan kebijakan Kementerian Perdagangan untuk menekan impor produk kain di era pasar bebas. Kata kunci : bea masuk tindakan pengamanan; kain; liberalisasi; perdagangan internasional